2005
DOI: 10.1177/1082013205056785
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Juices from Mature and Immature Acerola (Malpighia emarginata DC)

Abstract: Chemical composition and antioxidant activity of juice from immature and mature acerola and of concentrated juice from immature acerola were determined. Tartaric, malic and citric acids and a high content of ascorbic acid were found in all the juices. Vitamin C contents were 4.80, 1.90 and 0.97 g/100 g for the concentrated immature, the immature, and the mature acerola juices respectively. The total phenol contents decreased during ripening, from 3.8 mg of catechin/g for immature acerola juice to 1.4 mg of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 17 publications
3
42
1
8
Order By: Relevance
“…Estudos indicam que a contribuição do AA e dos fenólicos totais na atividade antioxidante de frutas pode depender do método escolhido e também das características hidrofóbicas ou hidrofílicas do sistema teste (RIGHETTO et al, 2005). Como relatado anteriormente, a atividade antioxidante in vivo de frutas tropicais não é resultado de um único componente fitoquímico, mas da soma deles, o que reforça a importância da variedade na composição de refeições, e expõe as limitações de proposições que valorizam, mais exclusiva e isoladamente, um ou outro componente específico da alimentação.…”
Section: Teor De Fenólicos Totaisunclassified
“…Estudos indicam que a contribuição do AA e dos fenólicos totais na atividade antioxidante de frutas pode depender do método escolhido e também das características hidrofóbicas ou hidrofílicas do sistema teste (RIGHETTO et al, 2005). Como relatado anteriormente, a atividade antioxidante in vivo de frutas tropicais não é resultado de um único componente fitoquímico, mas da soma deles, o que reforça a importância da variedade na composição de refeições, e expõe as limitações de proposições que valorizam, mais exclusiva e isoladamente, um ou outro componente específico da alimentação.…”
Section: Teor De Fenólicos Totaisunclassified
“…However, the lowest yields are obtained for the aqueous extracts. Howard et al 43 48 , who observed greater contents of flavonoids in red peppers than in green ones.…”
Section: Flavonoids and Flavonolsmentioning
confidence: 96%
“…It is well known that content of phytochemicals, including phenolic compounds present in vegetables, is affected by the specie and type of pepper, agronomic conditions, maturity 43 , postharvest handling and pre and postharvest treatments applied to the fruit 44 . …”
Section: Total Phenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Este fruto tiene alta demanda por el contenido de vitamina C, así como sus propiedades antioxidantes y nutrimentales (Dean et al, 1997;Hassimotto et al, 2005;Riguetto et al, 2005). La fructificación ocurre durante los meses de mayo a diciembre (Simão, 1971).…”
Section: Introductionunclassified